EVALUATION OF INDONESIAN ENGLISH TEXTBOOK FOR THE NINTH GRADERS OF JUNIOR HIGH SCHOOL “THINK GLOBALLY ACT LOCALLY” FROM EFL TEACHERS’ PERSPECTIVES - Sri Handayani; Bambang Suwarno; I Wayan Dharmayana (JOALL (Journal of Applied Linguistics and Literature), 2018)
The purpose of the study was  to investigate the EFL teachers’ perceptions concerning the textbook of “Think Globally Act Locally” on these criteria: (1) physical and utilitarian attributes, (2) efficient outlay of objectives and supplementary material, (3) learning- teaching content, (4) language skills and aspects. Thirty two EFL teachers of junior high school participated in this study. The instrument consisted of questionnaire and interview. Results indicated that in physical and utilitarian attributes, this textbook was perceived as ‘Good’, in efficient outlay and supplementary materials was perceived as   ‘Fair’,   in learning-teaching content was perceived as ‘Fair’,  and in language skills and aspects was perceived  as  ‘Fair’.  Overall,  this  textbook  was  perceived  as ‘Fair’.  It  still  needs improvement in several aspects. The illustrations should be more natural. The mistakes in this textbook should be corrected. Teaching aids like audio materials (cassette/CD), posters, and flashcards, need to accompany this textbook. The exercises should be varied. New word list and glossary should  be provided to support vocabulary building and reading   skill.   Finally,   authentic   audio   material   like   cassette/CD   and   phonetic transcriptions for each new word should be available for listening and pronunciation practice.